2017
DOI: 10.1101/171579
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correlated seed failure as an environmental veto to synchronize reproduction of masting plants

Abstract: Highly variable, synchronized seed production, called masting, is a widespread reproductive strategy in plants. Resource dynamics, pollination success, and, as described here, environmental veto, are possible proximate mechanisms of masting. We extended the resource budget model of masting with correlated and uncorrelated reproductive failure, and ran this model across its parameters space. Next, we parametrized the model based on a 16-year seed production data for red (Quercus rubra) and white (Q. alba) oaks.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
67
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(73 citation statements)
references
References 42 publications
5
67
1
Order By: Relevance
“…Past theoretical work concluded that environmental noise alone could not drive large-scale spatial synchronization of tree reproduction [62][63][64]. However, more recent theoretical models showed that if correlated environmental noise is replaced with reproduction failure caused by environmental veto, then large-scale synchronization may apply [58], a result supported by our study. A previous work relating airborne pollen dynamics to seed production in Q. ilex found that the onset of the flowering season had a strong effect on acorn production, while total pollen did not [37].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Past theoretical work concluded that environmental noise alone could not drive large-scale spatial synchronization of tree reproduction [62][63][64]. However, more recent theoretical models showed that if correlated environmental noise is replaced with reproduction failure caused by environmental veto, then large-scale synchronization may apply [58], a result supported by our study. A previous work relating airborne pollen dynamics to seed production in Q. ilex found that the onset of the flowering season had a strong effect on acorn production, while total pollen did not [37].…”
Section: Discussionsupporting
confidence: 80%
“…drought or synchrony-related pollination failure) decreases variability in seed production among trees both within-and among-sites (figure 3). Recently, environmental veto was incorporated into resource budget models, showing that it might be a driver of observed variability and synchrony of seed production [7,10,58]. Our results provide further empirical support for these models, showing that environmental veto is a likely driver of the large-scale synchrony of seed production observed in masting plants [33,34,59,60].…”
Section: Discussionsupporting
confidence: 73%
“…Early fruit abortion in European beech has, to our knowledge, not been previously reported. A recent study 14 , however, reported that environmental factors such as frosts can lead to a pollination failure via an "environmental veto", inhibiting fruit setting, mainly observed in oak trees. Our observations in European beech led to the conclusion that even if pollination in spring, and therefore fruit setting, is successful, subsequent fruit production can fail.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of frosts preventing trees from producing fruits has been described as an "environmental veto" and has primarily been observed in oak trees (Quercus sp.) 12,14,15 . According to Pearse et al 16 and Geburek et al 17 , European beech is a species which is controlled by flowering but not by fruit maturation.…”
mentioning
confidence: 99%
“…However, the pollination Moran effect (Pearse et al, ) may be more applicable as a mechanism of synchronization in oaks (Bogdziewicz et al, ). In support of a pollination Moran effect, Bogdziewicz, Steele, et al () showed that pollination failures caused by environmental vetoes could synchronize the dynamics of seed production among individual trees. The environmental veto hypothesis, according to which specific weather conditions can prevent individual trees from flowering or being pollinated over a substantial area, may thus be a plausible mechanism linking masting (seed production synchrony) with climate (Bogdziewicz, Steele, et al, ; Pearse et al, ).…”
Section: Introductionmentioning
confidence: 99%